Marketing Strategy on Community Based Tourism in Special Region of Yogyakarta - SUGANDINI, Dyah; EFFENDI, Mohamad Irhas; ARIBOWO, Agus Sasmito; UTAMI, Yenni Sri (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018DO - 10.14505//jemt.v9.4(28).06, 2018)
This research aims to analyze marketing strategy of tourism in Yogyakarta using SWOT analysis. This research is using Community Based Tourism (CBT) approach. CBT is the empowerment of local community where they are involved in the planning, managing, and decision making for the development. The urgency of this research is the demand from Indonesian government for tourism development in Special Region of Yogyakarta in order to make Yogyakarta as a leading tourism destination in Southeast Asia. This research is conducted in Yogyakarta that has four districts and one city. The data used in this research is primary and secondary data. The respondents are foreign and domestic tourists and stakeholders officials. The number of respondents is 300 people. The data is collected by convinience sampling. The secondary data analysis shows that foreign and domestic tourists who come to Special Region of Yogyakarta is relatively increasing in the last three years. Tourism destination in Special Region of Yogyakarta which based on community is also increasing and always innovating. The primary data analysis shows thattourism destination quality, satisfaction, and image according to the visitor perception is good, but the visitor loyaly shows a bad result. Most of the tourists visit Special Region of Yogyakarta just once and it is just a transit destination. The strategy that is necessary to increase the visit in tourism destination for tourists can be done through promotion of cultural destination that is quite attractive for the tourists. An integrated promotion for CBT needs to be more improved.